Calibration‐free quantitative immunoassay by flow cytometry: Theoretical consideration and practical implementation for IgG antibody binding to CD14 receptors on human leukocytes. Issue 7 (15th August 2018) - Khalo, Irina V.; Kozyreva, Viktoriya S.; Vakhrushev, Roman V.; Patlai, Daria S.; Shilova, Anna N.; Karpenko, Andrei A.; Yurkin, Maxim A.; Moskalensky, Alexander E.; Strokotov, Dmitry I.; Maltsev, Valeri P.; Chernyshev, Andrei V.
Abstract: We propose a calibration‐free method to determine the number of receptors per cell, as well as the direct and the reverse reaction rate constants for a single receptor. The method is based on the analysis of the temporal evolution of the cells mean fluorescent intensity measured by a flow cytometer during the ligand–receptor (antigen–antibody) binding under the conditions of their comparable concentrations. We developed the kinetic approach accounting both for the delay between the dilution and the measurement and for the practical duration of the measurement itself. The method was applied to determine thenumber of CD14 receptors on human blood mononuclear (granulocytes, monocytes, lymphocytes) cells of several donors. We also obtained the direct ( k + = (5.6 ± 0.2) × 10 7 M −1 min −1 ) and reverse ( k − = (1.3 ± 0.2) × 10 −2 min −1 ) rate constants of ligand–receptor interaction, and estimated the size of the binding site as b = 0.5 nm. The latter allows one to recalculate the rate constants for a different ligand, fluorescent label, medium viscosity, and/or temperature. The knowledge of the rate constants is essential for the calibration‐free determination of the number of receptors per cell from a single kinetic curve of the cells mean fluorescence intensity.